Culture Approach As Innovation In Development Of Infrastructure - Azima Dimyati; Selvi Diana Meilinda (Saburai International Journal of Social Sciences and Development, 2018)
The cultural approach to implementing public infrastructure policies is new. The approaches commonly used in implementing policies are structural approaches (organizational roles), procedural and management approaches (network planning and control; program evaluation and review techniques), behavioral approaches: communication, complete information at each stage and a political approach (interdepartemental aspects of politics). This shows that, the cultural approach is an innovation of policy implementation to establish a model of policy implementation innovation with a cultural approach, researchers investigate in a case study of a simultaneous village building program (GSM) in the Tulang Bawang regency of Lampung Province. This study uses a qualitative approach that describes and explains the symptoms and trends in phenomena that appear at the research location.The results obtained, the implementation of the GSMK program is based on the value of mutual cooperation which in local terms Lampung is called sakai sambayan. Sakai Sambayan, covering a broad understanding, such as mutual cooperation, help to help, tolerance to others and to others both morally and materially at times of pleasure and distress.This value provides a spirit in the implementation of the GSMK program in Tulang Bawang Regency. The GSMK program is a movement carried out by, from, and for the people of Tulang Bawang Regency to do good together in an effort to accelerate infrastructure development in 147 villages simultaneously throughout the Tulang Bawang Regency with a budget sourced from non-government organizations, private parties from each village and Community Direct Assistance (BLM) of the APBD of Tulang Bawang Regency. This program is considered quite successful by many people, the innovation of cultural approaches in the implementation of policies makes it an alternative so that policies can be successful and goals can be achieved.